Development of Joint Operating Agreements in the Oil and Gas industry, and their Key Provisions: A Brief Analysis - Mukit Kabil, Abdul (South Asian Journal of Social Sciences and Humanities, 2025)
A joint operating agreement (JOA) is a common practice by which companies join to form a joint venture in their oil and gas exploration and production. JOA is required mainly to mitigate high operational risks, costs and liabilities and to ensure the success of companies shared vision. Although it is a general idea that JOA has evolved from the form 610, devised by the American Association of Petroleum Landmen, JOAs also can be seen as a descendant of Production Sharing Agreement (PSA), which had the same elements as JOAs. As an important contract in the commercial relationship between the parties, the JOA must perform its functions in accordance with certain provisions inserted by the parties based on the agreed terms. The main aim of this article is to discuss the concept and development of JOA and to analyze the key provisions of a typical JOA. This research is conducted through a review of relevant literature and my academic experience gained during the LLM program on Oil and Gas Law at the University of Aberdeen.